Artificial Intelligence Empowers Solid-State Batteries for Material Screening and Performance Evaluation - Sheng Wang; Jincheng Liu; Xiaopan Song; Huajian Xu; Yang Gu; Junyu Fan; Bin Sun; Linwei Yu (Nano-Micro Letters)
Highlights The latest advancements in the application of machine learning (ML) for the screening of solid-state battery materials are reviewed. The achievements of various ML algorithms in predicting different performances of the battery management system are discussed. Future challenges and perspectives of artificial intelligence in solid-state battery are discussed.